The role of the International Criminal Police Organization (Interpol) in combating administrative and financial corruption - Khudhair, Wijdan Raham; fazaeli, Mstafa (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
With the growth of modern forms of organized crime, the role of the International Criminal Police Organization, which is considered the largest specialized police organization in the world in the field of combating transnational crime, appears through the development of cooperation and information exchange between its members and the tracking, prosecution and extradition of criminals. . Among the forms of organized crime is corruption, and in view of the negative effects it leaves on the international community as a result of the depletion of public resources thanks to corruption and its smuggling outside the country, and the subsequent laundering of that money, accordingly, the International Criminal Police Organization has drawn up an integrated strategy to combat this dangerous phenomenon by launching a number of initiatives Which aims to recover stolen assets, prevent and combat money laundering, and track down safe havens for the corrupt.